PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT MEGA BUANA INDAH DI KOTA BATAM - Ifandy, Rani; Siringoringo, Renniwaty (LPPM Universitas Putera Batam, 2019)
This study aims to determine the Effect of Motivation and Compensation on Employee Performance. This research was conducted at PT Mega Buana Indah in Batam City. The population in this study amounted to 156 people. In this study the sampling technique used is classified as a non probability sampling technique with a simple random sampling technique. By using the Slovin formula, the samples in this study were 113 respondents. The analytical tool used in this study is SPSS (Statistical Product and Services Solution) version 21. This study produces multiple linear regression equations and has R Square Value (R2) in this study of 38.2%. Based on the results of the t-test research partially obtained results that Motivation has a positive and significant effect on Employee Performance. Compensation has a positive and significant effect on Employee Performance. Based on the results of the F test, the results showed that Motivation and Compensation together had a positive and significant effect on the Employee Performance of PT Mega Buana Indah in Batam City.